The water method significantly enhances detection of diminutive lesions (adenoma and hyperplastic polyp combined) in the proximal colon in screening colonoscopy - data derived from two RCT in US veterans - Leung, Felix W (Landes Bioscience, 2011)
PURPOSE: Emerging data indicate a colonoscopist-controlled method is needed to avoid missing proximal colon pre-malignant lesions. Screening colonoscopy does not prevent all proximal colon cancers. Even diminutive lesions in the proximal colon harbor dysplasia. In addition to adenomas (presumptive cancer precursors), recent proposals to reevaluate proximal colon hyperplastic polyps as serrated polyps which could be pre-malignant or harbingers of interval neoplasia dramatize the importance of attending to these lesions. The finding that the water method increased yield of proximal diminutive adenomas prompted assessment of the hypothesis that the water method increases yield of all proximal diminutive lesions (adenoma and hyperplastic polyp) in screening cases. METHODS: Two RCT assessed the water method with primary outcome of completion of unsedated colonoscopy when the option of scheduled, unsedated or sedation on demand was used. Diminutive (<10 mm) lesions proximal to the splenic flexure were tracked. RESULTS: In screening cases, 31% and 6% of the water and air group had at least one proximal diminutive lesion (p=0.0012). Regression analysis revealed withdrawal time, method and volume of water used were significant predictors of proximal diminutive lesions. Effect of the water method on detection of proximal diminutive lesions was independent of age, body mass index, endoscopist, sedation, cecal intubation rate, bowel cleanliness score on withdrawal and total procedure time. LIMITATION: Male subject predominance, analysis of secondary outcomes of pooled RCT data. CONCLUSION: The hypothesis that the water method effectively enhances proximal diminutive lesion detection in screening colonoscopy in diverse clinical settings should be tested.